Ventricular Assist Devices or Inotropic Agents in Status 1A Patients? Survival Analysis of the United Network of Organ Sharing Database - Wozniak, Curtis J. (2014)
BACKGROUND: Improved outcomes as well as lack of donor hearts have increased the use of ventricular assist devices (VADs), rather than inotropic support, for bridging to transplantation. Recognizing that organ allocation in the highest status patients remains controversial, we sought to compare outcomes of patients with VADs and those receiving advanced medical therapy. METHODS: The United Network of Organ Sharing (UNOS) database was used to compare survival on the waiting list and posttransplantation survival in status 1A heart transplantation patients receiving VADs or high-dose/dual inotropic therapy or an intraaortic balloon pump( IABP), or both. Adjusted survival was calculated using Cox’s proportional hazard model. RESULTS: Adjusted 1-year posttransplantation mortality was higher among patients with VADs compared with patients receiving inotropic agents alone (hazard ratio [HR], 1.48; p < 0.05). Survival remained better for patients receiving inotropic agents alone in the post-2008 era (HR, 1.36; p = 0.03) and among those with isolated left-sided support (HR, 1.33; p = 0.008). When patients who received IABPs were added and analyzed after 2008, the left ventricular assist device (LVAD) group had similar survival (HR, 1.2; p =0.3). Survival on the waiting list, however, was superior among patients with LVADs (HR, 0.56; p < 0.05). In a therapy transition analysis, failure of inotropic agents and the need for LVAD support was a consistent marker for significantly worse mortality (HR, 1.7; p < 0.05). CONCLUSIONS: Although posttransplantation survival is better for patients who are bridged to transplantation with inotropic treatment only, the cost of failure of inotropic agents is significant, with a nearly doubled mortality for those who later require VAD support. Survival on the waiting list appears to be improved among patients receiving VAD support. Careful selection of the appropriate bridging strategy continues to be a significant clinical challenge.